An Economic Look at the Sustainability of FBS Athletic Departments - Fort, Rodney (Journal of Intercollegiate Sport, 2010)
In this descriptive historical review, I examine indicators of economic health for FBS athletic departments over time—attendance, media revenues, postseason revenues, operating revenues and expenses of athletic departments, and competitive balance. In addition, I review these and business management responses by athletic directors during the first year of the current recession. While there is some limited evidence that the recession of 2001 impacted BCS bowl payouts and revenues of the largest athletic departments, these rebounded quickly. Essentially, FBS athletic departments have been mostly impervious to business cycles. Implications are discussed.